ANALISIS TINGKAT KEPUASAN PENGGUNA WEBSITE E-LEARNING UINSU MENGGUNAKAN METODE SYSTEM USABILITY SCALE - Zaki Tausy Errahman Sitanggang; Nadil Fawwaz Ray; Irfan Yusuf; Ahmad Satria; M. Khalil Gibran (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
The development of information technology has had a significant impact on the world of education, particularly in the use of electronic-based learning systems, or e-learning. Universities have begun utilizing e-learning websites as online learning media to support academic processes such as material delivery, discussions, assignment submission, and online exams. However, the success of an e-learning system is determined not only by the completeness of its features, but also by the level of ease and comfort of use for users. This study aims to analyze the level of user satisfaction of the e-learning website at the State Islamic University of North Sumatra using the System Usability Scale (SUS) method. The study employed a descriptive quantitative method, with data collection techniques including observation, literature review, and distribution of SUS questionnaires to 50 active student users of the UINSU e-learning website. The results showed that the UINSU e-learning website obtained a SUS score of 57,45 which is in the below avarage category. These results indicate that the system meets usability aspects such as learnability, efficiency, and satisfaction, although some shortcomings remain in the navigation and interface. This research is expected to provide material for the evaluation and development of e-learning websites to make them more effective, efficient, and user-friendly. ABSTRAK Perkembangan teknologi informasi memberikan pengaruh besar terhadap dunia pendidikan, khususnya dalam penggunaan sistem pembelajaran berbasis elektronik atau e-learning. Perguruan tinggi mulai memanfaatkan website e-learning sebagai media pembelajaran daring untuk mendukung proses akademik seperti penyampaian materi, diskusi, pengumpulan tugas, dan ujian online. Namun, keberhasilan suatu sistem e-learning tidak hanya ditentukan oleh kelengkapan fiturnya saja, tetapi juga tingkat kemudahan dan kenyamanan penggunaan sistem oleh pengguna. Penelitian ini bertujuan untuk menganalisis tingkat kepuasan pengguna website e-learning Universitas Islam Negeri Sumatera Utara menggunakan metode System Usability Scale (SUS). Penelitian menggunakan metode kuantitatif deskriptif dengan teknik pengumpulan data berupa observasi, studi literatur, dan penyebaran kuesioner SUS kepada 50 mahasiswa aktif pengguna website e-learning UINSU. Hasil penelitian menunjukkan bahwa website e-learning UINSU memperoleh skor SUS sebesar 57,45 yang termasuk kategori dibawah rata-rata. Hasil tersebut menunjukkan bahwa sistem telah memenuhi aspek usability seperti learnability, efficiency, dan satisfaction, meskipun masih terdapat beberapa kekurangan pada aspek navigasi dan tampilan antarmuka. Penelitian ini diharapkan dapat menjadi bahan evaluasi dan pengembangan website e-learning agar menjadi lebih efektif, efisien, dan user friendly.